Dual effects of cardamonin/alpinetin and their acrolein adducts on scavenging acrolein and the anti-bacterial activity from Alpinia katsumadai Hayata as a spice in roasted meat. Issue 13 (13th June 2022) - Lu, Yang; Liu, Juan; Tong, Jiaqi; Zhang, Chenxiao; Duan, Yi; Song, Xiaoli; Lu, Yongling; Lv, Lishuang
Abstract : CAR and ALP can inhibit ACR in roasted pork by forming ACR adducts. Three adducts were synthesized, and CAR-ACR-1 and ALP-ACR showed antibacterial activity. In roasted pork containing 2% AKH, CAR-ACR-1 reached the MIC of E. coli and S. aureus . Abstract : Acrolein (ACR) is frequently produced by the thermal degradation of carbohydrates and amino acids and lipid peroxidation in the thermal processing of food. Long-term exposure to ACR can cause various chronic diseases. Here, we screened two high-temperature-resistant ACR inhibitors, cardamonin (CAR) and alpinetin (ALP), which can interconvert without any loss at 100 °C, and were obtained from Alpinia katsumadai Hayata (AKH). They demonstrated the best activity among the six spices investigated and could scavenge ACR generated in roasted pork by forming adducts. After three ACR adducts were prepared, namely CAR–ACR-1, CAR–ACR-2 and ALP–ACR, quantitative analysis showed that the amount of CAR–ACR-1 generated in lean roasted pork with 2% AKH addition reached the minimal inhibitory concentration against Escherichia coli and Staphylococcus aureus, which was 20 times lower than that of CAR, and the higher the generation of ACR, the stronger its antibacterial activity. These results provided well-defined evidence to promote the application of AKH to ACR inhibitors in food processing.